The determinants of spot gold price in Malaysia / DK Balqis Badrina AK Johari @ PG Johari - AK Johari@ PG Johari, DK Balqis Badrina (2022)
The purpose of this study is to investigate the link between selected Malaysian macroeconomic variables and the spot gold price. For this research, the macroeconomic factors include exchange rate, inflation rate, and crude palm oil price. The data used in this study took time series data on a quarterly basis period from 1991 to 2020 (30 years). Multiple Linear Regression (MLR) will be used in this research to evaluate macroeconomic factors influencing the spot gold price in Malaysia, as well as Correlation Coefficients to analyse the connection between these variables, and all data will be analysed using EViews 12. The findings for this study show that macroeconomic factors are significantly impacted to spot gold price which there is the existence of a positive correlation between the variables of exchange rate and crude palm oil price with spot gold price. On the other hand, the study also discovered a negative correlation between the inflation rate towards spot gold price. As a result, investors can make better investment judgments since they can refer the involvement of the spot gold price and macroeconomic factors that have been selected for this study. Keywords: Spot gold price; Exchange Rate, Inflation Rate: Crude Palm Oil Price; Multiple Linear Regression